DIAGNOSTIC AND INDICATION OF BLOOD TRANSFUSION IN APLASTIC ANEMIA - Fauzi, M Rizqa (E-Jurnal Medika Udayana; vol 2 no6(2013):e-jurnal medika udayana, 2013)
Aplastic anemia is a disease caused by a failure of the bone marrow to produce blood cells components resulting anemia with pancytopenia. symptoms will arise according to the blood cells decreased. Aplastic anemia is a rare and severe disease. The International Aplastic anemia and agranulocytosis Study found the incidence of aplastic anemia in Europe about 2 than 1,000,000 per year. Incidents in Asia 2 to 3 times higher than in Europe. In China, the incidence is estimated to 7 cases per 1,000,000 people and in Thailand is estimated to 4 cases per 1,000,000 people. The highest frequency at 15 and 25 years, the second highest peak at age 65 and 69 years. The cause of aplastic anemia majority (50-70%) is unknown. Enforcement of diagnosis based on history, physical examination, laboratory investigations and radiological either. One treatment in aplastic anemia is a blood transfusion. Blood transfusion in aplastic anemia is necessary when haemoglobin levels <7 g / dl and platelet count <20.000/?L. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: aplastic anemia, pancytopenia, haemoglobin, platelet